2018
DOI: 10.3390/ma11091611
|View full text |Cite
|
Sign up to set email alerts
|

Coating Formation on Ti-6Al-4V Alloy by Micro Arc Oxidation in Molten Salt

Abstract: Micro Arc Oxidation (MAO) is an electrochemical surface treatment process to produce oxide protective coatings on some metals. MAO is usually conducted in an aqueous electrolyte, which requires an intensive bath cooling and leads to the formation of a coating containing impurities that originate in the electrolyte. In the current work, we applied an alternative ceramic coating to the Ti-6Al-4V alloy using the MAO process in molten nitrate salt at a temperature of 280 °C. The obtained coating morphology, chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Wei Song [7] investigated the influence of a stable solid electrolyte mixed with a cellulose additive on the tribological performance of micro arc oxidation coatings. In general, micro arc oxidation is conducted in an aqueous electrolyte, however, Alexander Sobolev [8] applied an alternative MAO ceramic coating to a Ti-6Al-4V alloy in molten nitrate salt at a temperature of 280 • C. Not only the electrolyte type, but also the temperature of the electrolyte had a great influence on the coating quality. Wang Xuefei [9] studied the characterization of micro arc oxidation coatings on an aluminum alloy under different electrolyte temperatures, and found that the thickness and growth rate of the films decreased with the increase in electrolyte temperature, which led to a poor corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Wei Song [7] investigated the influence of a stable solid electrolyte mixed with a cellulose additive on the tribological performance of micro arc oxidation coatings. In general, micro arc oxidation is conducted in an aqueous electrolyte, however, Alexander Sobolev [8] applied an alternative MAO ceramic coating to a Ti-6Al-4V alloy in molten nitrate salt at a temperature of 280 • C. Not only the electrolyte type, but also the temperature of the electrolyte had a great influence on the coating quality. Wang Xuefei [9] studied the characterization of micro arc oxidation coatings on an aluminum alloy under different electrolyte temperatures, and found that the thickness and growth rate of the films decreased with the increase in electrolyte temperature, which led to a poor corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma electrolytic oxidation (PEO) as a rule is used to obtain oxides or mixed coatings on aluminium, titanium, magnesium alloys by using aqueous solutions of salts with polymeric anions – silicates 1, phosphates, tungstates, borates of alkali metals. In recent years, a new promising method of obtaining anticorrosion coating on the Ti−6Al−4V alloy in molten nitrate salt at a temperature of 280 °C was proposed …”
Section: Introductionmentioning
confidence: 99%
“…The basic principle of the MAO technology is an application of a high voltage between the treated metal and the electrode. During the process, micro-arc discharge migration points appear on the surface lead to the oxide coating formation [5,6,7,8]. Usually, MAO treatment is suitable for the enhanced mechanical properties and corrosion resistance of the alloys’ surface [9,10,11].…”
Section: Introductionmentioning
confidence: 99%